Pengaruh Jenis Fluor Topikal Terhadap Kebocoran Mikro pada Pit and Fissure Sealant - Hudiyati, Maya; Chairani, Shanty; Rais, Sri Wahyuningsih (Jurnal Material Kedokteran Gigi, 2016)
Prevention of dental caries in children can be done with topical fluoride as well as pit and fissure sealant. Topical fluoride application followed by pit and fissure sealant is still controversial because it allegedly could impair the bond between pit and fissure sealant materials to the teeth, so that it can lead to microleakage. The aim of this study was to determine the effect of 5% NaF and 1.23% APF on microleakage of RMGIC and flowable composite as pit and fissure sealant materials. Thirty extracted premolars were prepared and then divided into three groups: without topical fluoride, with application of 5% NaF (Enamelast, USA), and with application of 1.23% APF (60 Second Taste, USA); then filled using RMGIC (GC Fuji II LC, Japan) and flowable composite (Esthet.Xflow, USA). The teeth were soaked in methylene blue and then cut buccolingually. Microleakage was observed using stereomicroscope and scored in an ordinal scale. The Kruskal-Wallis test on RMGIC groups was not significant, while in the flowable composite groups was significant (p <0.05). Mann-Whitney test showed a significant difference between the RMGIC and flowable composite groups after application of 1.23% APF. It can be concluded that microleakage of pit and fissure sealant using a flowable composite was higher than RMGIC after application of 1.23% APF.